Preliminary Study of Reproduction of Dolphinfish Coryphaena hippurus Linnaeus, 1758 which exploited in the Maluku Sea, Eastern of North Sulawesi - Wagiu, Yohana R.; Rondonuwu, Arie B.; Bataragoa, Nego E.; Manginsela, Fransine B.; Manu, Gapar D. (Jurnal Ilmiah Platax, 2023)
This study aims to determine the sex ratio, gonad maturity level, gonad maturity index, and fecundity of dolphinfish Coryphaena hippurus.  Samples were obtained from the catches of fishermen who landed in Kalinaun Village. Fish and gonadal weight were measured with a digital scale with an accuracy of 0,1 gram and fork length was measured to an accuracy of 0.1 cm. Samples obtained were 60 individuals, 16 males with a size range of 40.5-57.4 cm and 44 females with a size range of 42.9-72.6 cm.  The sex ratio of males and females was 1:2.75.  The level of gonadal maturity of all samples was level II (developing) III (maturation) and IV (mature) for both males and females, level I (undeveloped) and V (saline) were not found. The gonadal maturity level was dominated by maturity level III (maturation) every month, except June when level IV for males was dominated.  The gonadal maturity index value of developing (level II) was 0.79 ± 0.37, level III was 3.62 ± 1.33 and level IV was 4.66 ± 0.65 for females. Level  II 0.28 ±0.18, level III 0.47 ±0.16 and level IV 0.63 ±0.06 for male. Fecundity ranged from 28,313-554,023 with an average of 229,839 ±139,967. Abstrak             Penelitian ini bertujuan untuk mengetahui nisbah kelamin, tingkat tematangan gonad, indeks kematangan gonad dan fekunditas ikan lemadang Coryphaena hippurus. Sampel diambil dari tangkapan nelayan yang didaratkan di Desa Kalinaun.  Berat ikan diukur dengan timbangan digital berketelitian 0,1 gram dan Panjang cagak diukur sampai ketelitian  0,1 cm. Sampel yang diperoleh sebanyak 60 individu, jantan 16 individu dengan kisaran ukuran 40,5-57,4 cm dan betina 44 individu dengan kisaran ukuran 42,9-72,6 cm.  Perbandingan kelamin jantan dan betina adalah 1:2,75.  Tingkat kematangan gonad dari seluruh sampel adalah tingkat kematangan II (berkembang) III (pematangan) dan IV (matang) baik jantan maupun betina, tingkat kematangan I (belum berkembang) dan V(salin)  tidak ditemukan. Tingkat kematangan gonad didominasi tingkat kematangan III (pematangan) setiap bulan, kecuali bulan Juni didiminasi TKG IV untuk jantan.  Nilai IKG  betina TKG II 0,79 ±0,37, TKG III 3,62 ±1,33 dan TKG IV 4,66 ±0,65. Ikan jantan TKG II 0,28 ±0,18, TKG III 0,47 ±0,16 dan TKG IV 0,63 ±0,06. Fekunditas berkisar 28.313-554.023 dengan rata-rata  229.839 ±139.967.